ENHANCING STUDENTS' LEARNING MOTIVATION THROUGH ADAPTED DIGITAL COMICS: AN EXPERIMENTAL STUDY OF GRADE 10 AT SMK PGRI PEKANBARU - Husnah, Aprilinia; hadriana, hadriana; Adanan, Mahdum (TELL - US JOURNAL, 2024)
This study aims to evaluate the effectiveness of using adapted digital comics to enhance student learning motivation at SMK PGRI Pekanbaru. The research was conducted in a vocational high school setting with participation from a group of students. An experimental method was employed, involving the measurement of student learning motivation before and after the intervention with digital comics. Data were collected through pre- and post-tests, student questionnaires, and expert validations. The data analysis included paired t-tests to assess the significance of changes in motivation scores and descriptive statistics for feedback and validation scores. The results indicated a significant increase in student learning motivation after using digital comics. The average pre-test score was 408 (SD = 15.3), while the average post-test score increased to 410 (SD = 14.8). Analysis using a paired t-test revealed a statistically significant increase (t(17) = 2.13, p = 0.045) with a small effect size (Cohen's d = 0.14). Media validation by experts indicated that the digital comics were highly valid, with an average score of 4.21 out of 5. Student feedback also showed high appreciation for the graphical and learning aspects of the digital comics, with an average score of 4.76 for the graphical aspect and 4.07 for the learning aspect. Overall, this study supports the use of digital comics as an effective educational medium to enhance student learning motivation. The digital comics not only captured students' interest but also helped them better understand the material. These findings provide a foundation for further development and use of digital comics in future educational contexts. It is recommended that educators consider incorporating digital comics into their teaching strategies to boost student engagement and learning outcomes.